Youth on Edge Facing Global Crises in Multicultural French Society - Cicchelli, Vincenzo; Octobre, Sylvie (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"In spite of political despair, a possibility of change arises if young people's will to participate in rebuilding solidarity is taken seriously. The book brings hope to the table without turning a blind eye to unevenly distributed structural uncertainties and the simultaneous presence of different suggestions for how to repair fractures in the social fabric-from pressures to assimilate to cosmopolitanism." -Anna Lund, Professor of Sociology, Stockholm University, Sweden "The material studied in this book is diverse and gives a nice sociological dimension to the question explored and in relation with youth and belonging in multicultural and global contexts. It proposes a nuanced account of youth and crisis in multicultural societies." -Hervé Tchumkam, Altshuler Distinguished Teaching Professor and Professor of French and Postcolonial Studies, Southern Methodist University, USA This book explores disrupted youth cohesion in France within the context of multiple ongoing global economic, migratory, social, political, and security-related crises. While these trends can be observed in numerous Western societies, France provides a unique case study of various anticosmopolitan and anti-Enlightenment movements shaping youth conditions and reconfiguring relationships between the individual, the group, and society. The authors undertook in-depth interviews with French young people between the ages of 18 to 30 years old to inquire into how they experience "vivre ensemble" (living together) in a time of rising economic inequalities and multicultural tensions. Through these findings, they invite decision-makers, politicians, educators, and parents to propose a renewed narrative of social cohesion for youth who are not disillusioned, but deeply on edge.
1 Introduction: Does a Globalized Society Produce a Youth on Edge? -- 1 Toward a New Narrative -- 2 Youth at the Intersection of Global Crises -- 3 Open to the World, but Rooted in National Experience -- 4 How to Live Together -- 5 Voicing Tensions -- 6 A Survey Conducted in Two Phases -- 7 Conclusion -- Bibliography -- Part I Living Together in a Time of Global Crisis -- 2 A Time of Uncertainty -- 1 Terrorism and Demands for Increased Security -- 2 Immigration and Identity -- 3 Economic Ultraliberalism and Widening Inequalities -- 4 Anti-liberal Practices and the Decline of the National Community -- 5 The Crisis of Multilateralism and the Rise of Nationalism and Populism -- 6 Conclusion -- Bibliography -- 3 A Time of Fragmentation -- 1 Globalization and the Pitfalls of Academic Meritocracy -- 2 Globalization and the Losers of Integration in the Workplace -- 3 Globalization and Immigration -- 4 Globalization and the Recognition of Multiculturalism -- 5 Globalization and Challenges to the Principle of Solidarity -- 6 Globalization and Setbacks to a Shared Political Vision -- 7 Conclusion -- Bibliography -- 4 A Time of Tension -- 1 Wanderlust and National Sentiment -- 2 Inequalities at Work and Demands for Social Protection -- 3 Fluctuations in Openness on Immigration and the Multicultural Society -- 4 Intolerance with Regard to Inequalities and Injustices -- 5 Apathy and Political Engagement -- 6 Conclusion -- Bibliography -- Part II Living Together in a Changing Society -- 5 Freedom at the Risk of Decadence -- 1 The Progressives: More Civil Rights for All -- 2 Caught in the Middle: Adapting Norms to Reality -- 3 The Conservatives: The Price of Change and the Limits of Individual Autonomy -- 4 Conclusion -- Bibliography -- 6 Inequality at the Risk of Ultraliberalism -- 1 An Unequal France -- 2 Greater Demand for State Intervention -- 3 Letting Economic Forces Operate Freely -- 4 Conclusion -- Bibliography -- 7 Democracy at the Risk of Populism -- 1 Tired of Being Democrats -- 2 Tired of Democracy -- 3 Reinventing Politics -- 4 Conclusion -- Bibliography -- Part III Living Together in a Plural Society -- 8 Homo nationalis and the Nation's Singularity -- 1 The Spirit of Homo nationalis -- 2 Those Left Behind by Globalization -- 3 Those Worried About Downward Social Mobility -- 4 The Executives or Ideologists of Nationalism -- 5 Converts to the Nation -- 6 Conclusion -- Bibliography -- 9 Homo civicus and the Republican Canopy -- 1 The Spirit of Homo civicus -- 2 Between the Republic and the Nation -- 3 The Republic as a Driver of Integration -- 4 The Republic as a Path Toward Integration -- 5 Conclusion -- Bibliography -- 10 Homo culturalis and Cultural Diversity -- 1 The Spirit of Homo culturalis -- 2 Multiculturalism in Praise of Multiple Identities -- 3 Multiculturalism Used to Counter the Failures of the French Republic -- 4 Communitarian Multiculturalism -- 5 Conclusion -- Bibliography -- 11 Homo pontifex and Universal Humanity -- 1 The Spirit of Homo pontifex -- 2 Indifference to Difference -- 3 Ecumenism and Rootedness -- 4 Cosmopolitanism as Emancipation -- 5 Conclusion -- Bibliography -- In Guise of Conclusion.
Keywords: Sociology; Social groups; Youth-Social life and customs; Culture; Europe-Politics and government; Comparative government; Sociology of Family, Youth and Aging; Youth Culture; Sociology of Culture; European Politics; Comparative Politics